«Estro furioso» : Domenico Rea from Naples to Nofi - Salerno, Vincenzo; Bellissimo, Oriana; Rimolo, Eleonora (Orione. Studi e testi di Letteratura italiana, 2022)
«Estro furioso» is the title of one of the twelve short-stories making up the index of Gesù, fate luce, the second book by Domenico Rea published in 1950; three years after its 'official' debut, always with a collection of short narrative texts, in prose: Spaccanapoli. And, again, the expression "Estro furioso" could now be used: as a 'sample' of style - or as a possible outline of shared reading - in the five chapters (Domenico Rea as contemporary writer; Domenico Rea, poet and novelist; Domenico Rea between national and regional publishing; Domenico Rea among History, Anthropology, Journalism and Photography; Domenico Rea between the Old and the New Continent: the language, the literature) thematic containers of fifteen essays of this volume dedicated to Domenico Rea. The authors of the essays are scholars from various Italian and foreign universities, journalists, experts in the world of photography and publishing.